Les formations supérieures françaises délocalisées à l’étranger : Expériences migratoires d’étudiants français au Vietnam - Sophie Cerbelle (Éducation et Socialisation)
More and more French students go abroad for studying. At the same time, France is considering proposal to make export of its higher education. Few research focuses on French students enrolled in French decentralized training in developing geographic areas. It is the main purpose of this research which aims to better understand school and social integration of French students enrolled in French training in Vietnam and provide opportunity to raise question regarding French training offer abroad.